Synthesis and evaluation of novel prenylated chalcone derivatives as anti-leishmanial and anti-trypanosomal compounds - Passalacqua, Thais Gaban [UNESP]; Dutra, Luiz Antonio [UNESP]; Almeida, Letícia de [UNESP]; Velásquez, Angela Maria Arenas [UNESP]; Torres, Fábio Aurélio Esteves [UNESP]; Yamasaki, Paulo Renato [UNESP]; Santos, Mariana Bastos dos [UNESP]; Regasini, Luis Octavio [UNESP]; Michels, Paul A. M.; Bolzani, Vanderlan da Silva [UNESP]; Graminha, Marcia A. S. [UNESP] (Elsevier B. V., 2015)
Chalcones form a class of compounds that belong to the flavonoid family and are widely distributed in plants. Their simple structure and the ease of preparation make chalcones attractive scaffolds for the synthesis of a large number of derivatives enabling the evaluation of the effects of different functional groups on biological activities. In this Letter, we report the successful synthesis of a series of novel prenylated chalcones via Claisen-Schmidt condensation and the evaluation of their effect on the viability of the Trypanosomatidae parasites Leishmania amazonensis, Leishmania infantum and Trypanosoma cruzi.
Keywords: Drug discovery; Leishmania amazonensis; Leishmania infantum; Leishmanicidal activity; Prenylated chalcone; Trypanocidal activity; Trypanosoma cruzi